2013
DOI: 10.1080/10158782.2013.11441515
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of staphylococcus aureus bacteraemia at Tygerberg hospital

Abstract: South Afr J Epidemiol Infect Original Research: Characterisation of Staphylococcus aureus bacteraemia at Tygerberg hospitalTo elucidate the local epidemiology of Staphylococcus aureus bacteraemia, we characterised blood culture isolates using molecular methods and prospectively collected clinical data to determine the occurrence of community-acquired, methicillinresistant S. aureus (MRSA). Consecutive S. aureus blood culture isolates were collected over a one-year period from patients who were admitted to Tyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…These were previously reported as dominant in these provinces (6). The spa-type CC 012 in these two provinces was similar to a study from Tygerberg Academic Hospital (16). When the six most common spa-types (t037, t1257, t012, t045, t064 and t032) and SCCmec types were correlated, SCCmec types II, III, IV and V and all six spa-types were linked to hospital-associated infections.…”
Section: Discussionsupporting
confidence: 80%
“…These were previously reported as dominant in these provinces (6). The spa-type CC 012 in these two provinces was similar to a study from Tygerberg Academic Hospital (16). When the six most common spa-types (t037, t1257, t012, t045, t064 and t032) and SCCmec types were correlated, SCCmec types II, III, IV and V and all six spa-types were linked to hospital-associated infections.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, spa-typing revealed 47 different spa-types with the five most common spatypes (t037, t1257, t045, t064 and t012) accounting for 87% and the most common ST was ST612 clonal complex (CC8) (n = 7) followed by ST5 (CC5) (n = 4), ST36 (CC30) (n = 4) and ST239 (CC8) (n = 3). Findings from this study correlated with previous studies in South Africa [25][26][27]. This study demonstrated the importance of monitoring molecular typing trends to detect changing epidemiological trends in antimicrobial resistance patterns [24].…”
Section: Molecular Diagnostics and Typing In South African Surveillansupporting
confidence: 87%
“…Certain pandemic MRSA clones are spread worldwide. Recent publications describe the ST612-MRSA-IV clone (MLST CC8) as the most widespread MRSA clone in Cape Town, and South Africa (Jansen van Rensburg et al, 2011;Orth et al, 2013;Oosthuysen et al, 2013;Moodley et al, 2010). In this study ST 612 formed strong biofilms, which may contribute to its dominance in nosocomial infections in South Africa.…”
Section: Discussionmentioning
confidence: 69%